Hemoplasma infection in wild captive carnivores - Carneiro,Filipe T. (2020)
ABSTRACT: Hemoplasmas are bacteria able to adhere themselves loosely to the plasma membrane of erythrocytes and may parasitize several species of mammals. There are three known species of hemoplasmas that parasitize domestic and wild cats: Mycoplasma haemofelis, ‘Candidatus Mycoplasma haemominutum’ and ‘Candidatus Mycoplasma turicensis’. Dogs are infected by at least two species of hemoplasmas: ‘Candidatus Mycoplasma haematoparvum’ and Mycoplasma haemocanis. The hemoplasmoses are very important in veterinary clinics, either because of its worldwide distribution and severity of clinical signs, depending on parasite species and host immune competence, or due to its zoonotic potential and capability of infecting endangered species. This study set out to investigate which hemoplasmas species parasitize different captive wild carnivores in order to clarify the epidemiology of hemoplasmoses in wild animals. Furthermore, the research intended to characterize the hematological changes caused by different species of hemotropic mycoplasmas infection in order to establish their clinical importance to wild species and the capacity of these species to become a reservoir of studied agents. Samples of 33 wild felids and 18 wild canids were investigated using polymerase chain reaction (PCR) to detect hemoplasmas DNA and it was observed that the occurrence of infection in these species is 45.5% and 83.3%, respectively. Factors such as age, gender or anaemia are not more frequent in animals positive for the infection. Therefore, it is concluded that infection caused by hemoplasmas in wild carnivores has high prevalence, and either agent pathogenicity is low, or chronic stage is more frequent, resulting in a low rate of diagnosis.